PKS 2131-021-Discovery of Strong Coherent Sinusoidal Variations from Radio to Optical Frequencies: Compelling Evidence for a Blazar Supermassive Black Hole Binary - Kiehlmann, S.; de la Parra, P. V.; Sullivan, A. G.; Synani, A.; Liodakis, I.; Mroz, P.; Naess, S. K.; Readhead, A. C. S.; Begelman, M. C.; Blandford, R. D.; Chatziioannou, K.; Ding, Y.; et al. (IOP Publishing Ltd, 2025)
Haystack and Owens Valley Radio Observatory observations recently revealed strong, intermittent, sinusoidal total flux-density variations that maintained their coherence between 1975 and 2021 in the blazar PKS 2131-021 (z = 1.283). This was interpreted as possible evidence of a supermassive black hole binary (SMBHB). Extended observations through 2023 show a coherence over 47.9 yr, with an observed period P-15 GHz = (1739.8 +/- 17.4) days. We reject, with p-value = 2.09 x 10(-7), the hypothesis that the variations are due to random fluctuations in the red noise tail of the power spectral density. There is clearly a physical phenomenon in PKS 2131-021 producing coherent sinusoidal flux-density variations. We find the coherent sinusoidal intensity variations extend from below 2.7 GHz to optical frequencies, from which we derive an observed period P-optical = (1764 +/- 36) days. Across this broad frequency range, there is a smoothly varying monotonic phase shift in the sinusoidal variations with frequency. Hints of periodic variations are also observed at gamma-ray energies. The importance of well-vetted SMBHB candidates to searches for gravitational waves is pointed out. We estimate the fraction of blazars that are SMBHB candidates to be >1 in 100. Thus, monitoring programs covering tens of thousands of blazars could discover hundreds of SMBHB candidates.